Carnitine palmitoyltransferase 1 (CPT1) alleviates oxidative stress and apoptosis of hippocampal neuron in response to beta-Amyloid peptide fragment Aβ25-35. Issue 1 (1st January 2021) - Ding, Yiyun; Zhang, Hongxia; Liu, Zhaojun; Li, Qiuping; Guo, Yujiao; Chen, Ye; Chang, Yue; Cui, Hongyan
ABSTRACT: CPT1C, which is expressed in hippocampus, influences ceramide level, endogenous cannabinoid and oxidation process, as well as plays an important role in various brain functions such as learning. This study aimed to investigate the role of CPT1C in Alzheimer's disease (AD) and its underlying mechanism. We established a model of Alzheimer's disease in vitro by exposing primary hippocampal neurons to beta-Amyloid peptide fragment 25–35 (Aβ25-35 ). The cell viability, lactate dehydrogenase (LDH) level, expressions of reactive oxygen species (ROS), malondialdehyde (MDA) and superoxide dismutase (SOD) were detected using Cell Counting Kit-8 (CCK-8), LDH assay, ROS kits, malondialdehyde (MDA) kits and SOD kits, respectively. Moreover, the expression of oxidative stress-related proteins as well as the expressions of amyloid precursor protein (App), p-Tau andβ-site APP-cleaving enzyme1 (Bace-1) were measured using quantitative reverse transcription PCR (RT-qPCR) and western blot. Tunel and western blot were adopted to detect apoptosis as well as its related proteins. After the treatment of peroxisome proliferators-activated receptor alpha (PPARα), CPT1C expression was detected with the application of RT-qPCR and western blot. CPT1C expression was reduced in Aβ25-35 -induced HT22 cells. Overexpression of CPT1C relieved cell viability and toxic injury as well as attenuated oxidative stress, apoptosis and expression levels of AD marker proteins. Moreover, higher doses of PPARα agonist activate the expression of CPT1C in Aβ25-35 -induced HT22 cells. In conclusion, CPT1C alleviates Aβ25-35 -induced oxidative stress, apoptosis and deposition of AD marker proteins in hippocampal neurons, suggesting that CPT1C has favorable effects on alleviating AD and participates in PPARα activation.